2007
DOI: 10.1002/ejsp.473
|View full text |Cite|
|
Sign up to set email alerts
|

Identity affirmation and social movement support

Abstract: It is argued that the power of collective identification to mobilize people for collective action such as social movement support derives at least partly from processes of identity affirmation. The hypothesized identity-affirming function of social movement support is tested in two laboratory experiments which revolve around collective identity as a supporter of the peace movement. In Experiment 1, we predicted and found that people who strongly identified with the peace movement showed more movement support (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
29
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 20 publications
1
29
0
2
Order By: Relevance
“…Collective action can also serve to identify the in‐group as a distinct entity and affirm its dissimilarity from the offending out‐group who unjustly mistreats or oppresses the in‐group. The general point is that collective action can raise the psychological meaning and the perceived status of the in‐group by demonstrating that it is a viable agent, distinct from the oppressive out‐group, even when these actions have no discernable impact on the actual status, resources or the physical realities of the group (see Drury & Reicher; Louis; Simon, Trötschel, & Dähne, 2008).…”
mentioning
confidence: 99%
“…Collective action can also serve to identify the in‐group as a distinct entity and affirm its dissimilarity from the offending out‐group who unjustly mistreats or oppresses the in‐group. The general point is that collective action can raise the psychological meaning and the perceived status of the in‐group by demonstrating that it is a viable agent, distinct from the oppressive out‐group, even when these actions have no discernable impact on the actual status, resources or the physical realities of the group (see Drury & Reicher; Louis; Simon, Trötschel, & Dähne, 2008).…”
mentioning
confidence: 99%
“…Simon, Trötschel, and Dähne (2008) conceptualize these two roles as either a "push" to participate from membership in a pre-existing collective identity or a "pull" to participate in order to gain an attractive collective identity: "In the first case I already occupy a place or position in the social world which makes participation for me the natural thing to do. In the second case I am still on my way to that place" (p. 945).…”
Section: Collective Identity's Uses In Mobilizationmentioning
confidence: 99%
“…Social psychological research on collective action has a relatively short history. The study of collective phenomena has long been located in the realm of sociological theory and research (e.g., Simon, Trötschel, & Dähne, 2008). Mirroring this, the first paper on collective action in EJSP was published in 1993 by Kawakami and Dion.…”
Section: An Overview Of Theory and Research On Collective Action In Tmentioning
confidence: 99%
“…De Weerd and Klandermans (1999) illustrated that identification with farmers at the national or regional level is an important predictor of participation in political protest. Furthermore, Simon, Trötschel, and Dähne (2008) demonstrated that collective action participation can be regarded as an identity affirmation strategy that expresses and confirms a desired but uncertain social identity.…”
Section: Collective Identification As Predictor Of Collective Actionmentioning
confidence: 99%